The integration principle, article 2 Colombian Criminal Code: guarantee from the accused or punishment tool? (2012)
The integration principle has been one of the multiple tools in which the ideals of Criminal law’s expansion have been supported to justify its proceeding; however, this principle obeys the need of reduce punitive power, more than a reason to expand the C